Design and Construction of Wind Turbine-Solar Panel System Prototype for Water Supply Control - Yunus, A.M Shiddiq; Mulyadi, Musrady; Apollo, Apollo; Rinaldi Wahid, Rifqy; Zalsabillah, Rima (INTEK: Jurnal Penelitian, 2021)
Water supply is a crucial for human lives, not only for daily activities but also for secondary purposes such as for watering garden, paddy fields etc. There are many efforts of human in fulfilling their water supply needs. Most of water supply is provided by using electric motor pumps which in certain cases might increase the financial cost. In this paper, wind energy is applied to pumping water mechanically whilst it combines with solar panel which works to pump water during less wind speed condition. The micro-controller Arduino-Uno is employed to manage the collaboration operation between wind and solar panel. The design concept and construction are presented and discussed. The operation results exhibit good operation performance and could be developed for the real application.